A Comparative Analysis of the Development of Russia, the United States, Europe, and China: An Interview with Michael Alexeev. Issue 2 (3rd March 2016) - Alexeev, Michael
Abstract : In the interview, Michael Alexeev compares the economics of transition to market-type systems.